The Empirical Study on the Relationship Between Market Indices Against the Chinese Market Index with the EPU as the Intervening Variable - Yeoh Wee Win (International Journal of Asian Business and Management, 2023)
This study aimed to explore the empirical study on the relationship between the foreign market indices against the Chinese market index with the EPU as the intervening variable where the study is targeted to provide the significant contribution to the academic as well as the investors to understand the movement of the stock market index. The previous study posed the strong suggestion on the potential positive correlation exist between the performance of the market indices with the economic policy uncertainty (EPU) being the effective intervening variable that will draw the expected of the result in the study forming the hypothesis for the study. The research methodology of quantitative method observes the application of the SPSS to analyze the data input for the secondary data collected for the market indices and EPU from 2012 to 2021 to be used to sum up the findings and result for the study. The outcome of the research findings had pointed out that the lack of suggestion with the previous study where the hypothesis is not accepted showing the opposite output had been achieved from the outcome of the study. With this, the study is summarized with the reflection on the literature review against the current findings before proceeding to draw the contribution of study as well as the suggestion for the future study that open opportunities for the future researchers